A Stress and Strain Relationship for Cylinder Concrete Containing Palm Oil Fuel Ash (POFA) and Expanded Polystyrene (EPS) - Muhamad Ikmal Haqeem Lokman; Osman, Mohamad Hairi; Mahyeddin, Mohd Eizzuddin (Progress in Engineering Application and Technology, 2022)
In this world, concrete is the most important component for building construction. The purpose of the concrete has remained constant across time, but the component of the concrete has changed. As a result, various innovative ideas and a revolution in modified concrete have been implemented. This will help to reduce the use of natural resources such as gravel and river sand in concrete mixes. In this study, Palm Oil Fuel Ash (POFA) will be implemented as a cement replacement, while Expanded Polystyrene (EPS) will be applied as a fine aggregate replacement in the concrete mixture. This research analyses the stress and strain of a concrete cylinder containing POFA and EPS with replacement percentages of 0% (control sample), 10%, and 20%. The objective of this research is to study the relationship of stress and strain for concrete containing EPS and POFA, to compare the exile comprehensive strength of concrete containing EPS and POFA with normal, and to establish the elasticity value of EPS and POFA containing concrete.